The Influence of Annealing and Doping by Copper on Electrical Conductivity of CdTe Thin Films - . K.H.Al-Maiyaly, Bushra (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research CdTe and CdTe: Cu thin films with different doping ratios (1, 2, 3, 4 and 5) %, were deposited by thermal evaporation technique under vacuum on glass substrates at room temperature in thickness 450 nm. The measurements of electrical conductivity (σ), and activation energies (Ea1, Ea2), have been investigated on (CdTe) thin films as a function of doping ratios, as well as the effect of the heat treatment at (373, 423, and 473) K° for one hour on these measurements were calculated and all results are discussed. The electrical conductivity measurements show all films prepared contain two types of transport mechanisms, and the electrical conductivity (σ) increases whereas the activation energy (Ea) would decrease as the increasing (Cu) percentage in the sample except 5%. It is also noticed that the electrical conductivity (σ) showed a decreasing trend with increasing annealing temperature, while the activation energies (Ea1, Ea2) showed opposite trend, where the activation energies increased with annealing temperature. Also the electrical conductivity values was found increased about 3- 4 orders when pure CdTe films are doped with (3, 4) % Cu and annealing at 473 K°.